INTERAKSI NEGARA DENGAN DUNIA PENDIDIKAN ISLAM DARI MASA KE MASA - Supandi, Supandi (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2017)
For about 15 centuries ago, Islamic history has portrayed the face of the true condition of Islamic education, not only describes the reality of past events, but also serves as a guide for the next generation, in order to make a better footing. Basically, with the coming of Islam in this archipelago, because one of them through education, beside through trade and marriage. The role and gait of Islamic education in seizing and uniting the archipelago into a country that is currently called Indonesia of course very much. Thus, in this paper, the author reveals a bit about the history of Islamic education in the old order, the new order and even during the current order of reform. The state has enormous power in governing and running the wheels of government, including in the world of Islamic education, so, the condition of Islamic education from the time of kemasanya have position and even a very different portion of the government which then has implications for the implementation of Islamic education.